Therapeutic Potential of Novel Silver Carbonate Nanostructures in Wound Healing and Antibacterial Activity Against Pseudomonas chengduensis and Staphylococcus aureus - Tehmina Khan; Ali Umar; Zakia Subhan; Muhammad Saleem Khan; Hafeeza Zafar Ali; Hayat Ullah; Sabeen Sabri; Muhammad Wajid; Rashid Iqbal; Mashooq Ahmad Bhat; Hamid Ali (MDPI AG, 2024)
Background/Objectives: Metallic NPs have been explored for various therapeutic uses owing to utilitarian physicochemical characteristics such as antibacterial, anti-inflammatory, and healing properties. The objective of this study is to evaluate the therapeutic potential of novel silver carbonate nanostructures in promoting wound healing and their antibacterial activity against Pseudomonas chengduensis and Staphylococcus aureus. Methods: In this work, we prepared Ag2CO3 nanoparticles through a two-step methodology that was expected to improve the material's biomedical performance and biocompatibility. The characterization and assessment of synthesized NPs biocompatibility were conducted using hemolysis assays on the blood of a healthy male human. Further, we performed molecular docking analysis to confirm interactions of silver NPs with biological molecules. Results: In detail, the synthesized NPs showed <5% hemolysis activity at various concentrations, confirming their therapeutic applicability. Additionally, the NPs had good metabolic activities; they raised the T3/T4 hormone content and acted effectively on Insulin-like Growth Factor 1 (IGF-1) in diabetic models. They also facilitated the rate of repair by having the diabetic wounds reach 100% re-epithelialization by day 13, unlike the control group, which reached the same level only by day 16. The synthesized Ag2CO3 NPs exhibited high antimicrobial potential against both Pseudomonas chengduensis and Staphylococcus aureus, hence being a potential material that can be used for infection control in biomedical tissue engineering applications. Conclusions: These findings concluded that novel synthesis methods lead to the formation of NPs with higher therapeutic prospects; however, studies of their metaphysical and endocrinological effects are necessary.